The Regulatory Amalgamation for Nursing and Midwifery in British Columbia - Kathleen Leslie; Cecilia Benoit; Angela Freeman; Ivy Bourgeault (McMaster University Library Press, 2021)
On 1 September 2020, Canada's first combined nursing-midwifery regulator was created with the amalgamation of the separate nurse and midwife regulators in British Columbia (BC). The highly critical Cayton Report on health profession regulation, the previous experience of amalgamating nursing regulators in BC, and a broader call for more efficient and effective regulation were factors influencing this reform. The goals of the reform were to increase regulatory efficiency (by maximizing economies of scale) and effectiveness (by ensuring adequate resources to meet the public interest mandate) and, for the regulators, to control the pace and progress of the amalgamation ahead of impending government dictate. These goals of the regulators' proposal to amalgamate clearly fit with the BC government's vision for modernizing health profession regulation. To implement the amalgamation, the BC government released an Order in Council on 8 June 2020 that amended various regulations under BC's Health Professions Act and confirmed the September 1 date of amalgamation. There is currently no clearly articulated evaluation plan for this reform; however, evaluating regulatory efficiency and effectiveness in the interests of the public is likely to be a focus moving forward for both regulators and governments.